2017
DOI: 10.17129/botsci.1111
|View full text |Cite
|
Sign up to set email alerts
|

Floristic, vegetational and geographic characteristics of the Sierra de Chiconquiaco, Veracruz, Mexico

Abstract: Background: Explored botanically from the 19th century, the Sierra de Chiconquiaco is recognized for its large vegetal and topographical heterogeneity. However, the available floristic information is sparse and its geographic characteristics remain undefined. The objective of this study was therefore to integrate floristic, vegetal and geographic information in order to identify areas that have experienced floristic exploration as well as potential sites for conservation. Question: Under which criteria can the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This is due to the short distance between the coastal zone and the elevations of the mountain range, which rises from thirty-five to almost 3,000 m a.s.l. [ 33 ]. The biodiversity of this area is threatened due to several activities, such as deforestation, forest fires, livestock, and agriculture, particularly in the mountains [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the short distance between the coastal zone and the elevations of the mountain range, which rises from thirty-five to almost 3,000 m a.s.l. [ 33 ]. The biodiversity of this area is threatened due to several activities, such as deforestation, forest fires, livestock, and agriculture, particularly in the mountains [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This area is topographically and climatically complex, with seven types of vegetation. It possesses a high plant diversity with 3019 species, including thirty-six endemic, 57 protected by Mexican laws, and 195 listed in CITES (including six cycads) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the short distance that exists between the coastal zone and the elevations of the mountain range, which rises from thirty-five to almost 3,000 m a.s.l. [34].…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the short distance that exists between the coastal zone and the elevations of the mountain range, which rises from thirty-five to almost 3,000 m a.s.l. [34]. The biodiversity of this area is threatened due to several activities such as deforestation, forest fires, livestock and agriculture, particularly in mountains [35].…”
Section: Study Areamentioning
confidence: 99%
“…The first collections of the species (previous to 2017) have been lost due to the death of Miguel Cházaro. During one decade of botanical explorations in the Cerro de la Magdalena Mountain and adjacent regions for floristic inventories and species descriptions ( Lascurain–Rangel et al 2017 ; Francisco-Gutiérrez et al 2023a ), very few specimens have been found and collected in the same locality of the type, some of them preserved as sterile material. The new species grows on very tall Quercus glabrescens ( Fagaceae ) trees, at altitudes of 3–6 m. It is distributed in the remnants of very humid pine-oak forests at elevations from 2,900 to 2,950 m. This species inhabits a zone of cloud forests on cliffs with strong winds rising from the Sierra de Chiconquiaco, Veracruz.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%